Odpowiedzi

  • Użytkownik Zadane
2010-04-11T12:58:21+02:00
X+8=-4
x = -4 -8
x = -12
SPR:L: x + 8 = -12+8 = -4
P: -4
L=P

6x-15=-7x-14
6x+7x=-14+15
13x=1
x=1/13
L:6/13-15 = -14 i 7/13
P: -7x-14 = -7/3 -14 = -14 i 7/13
L=P

2(x-1)-3(x+1)=-8
x-2-2-3x+2=-8
-2x = -8+2
-2x = -6 |:(-2)
x=3
L: 2(3-1) - 3(3+1) = 6-2-9-3= -8
P: -8
L=P
2010-04-11T13:05:29+02:00
A) x+8=-4
x=-4-8=-12
-12+8=-4
-4=-4

b) 6x-15=-7x-14
-15+14=-7x-6x
-13x=-1
x=1/13
6*(1/13)-15=-7*(1/13)-14
-14 i 7/13=-14 i 7/13

c) 2(x-1)-3(x+1)=-8
2x-2-3x+3=-8
x=9
2(9-1)-3(9+1)=-8
18-2-27+3=-8
-8=-8